Analysis of the Implementation of the Work Ethic of the Regional Office of the Ministry of Religion of North Sumatra - Fauzan Fahmi Hasibuan; Sri Sudiarti (Penerbit Jurnal Indonesia, 2022)
Human resources as one of the factors that play an important role in the success or failure of the organization in achieving its goals. Ensure that every organization always wants to move forward with the participation of its members to improve the quality of its performance, including that every organization has a work ethic. A person's attitude towards work that is practiced from business ethics is a view. The work ethic of a person or employee is a source of motivation for his actions. The purpose of this research is to analyze the work ethic of the Regional Office of the Ministry of Religion of North Sumatra. The analytical method used is descriptive qualitative. Overall, the descriptive statistics analysis of the results shows that in general the work ethic of the Regional Office of the Ministry of Religion of North Sumatra fulfills the mandate of providing services to the community in accordance with the applicable regulations.